Dyspnea During In-Hospital Rehabilitation as a Predictor of Rehospitalization and Mortality in Patients With Acute Heart Failure. Issue 5 (September 2019) - Yoshimura, Kae; Hiraoka, Arudo; Saito, Kazuya; Urabe, Yukio; Maeda, Noriaki; Yoshida, Toshinobu; Hayashida, Akihiro
Abstract : Purpose: Consensus articles that explore rehabilitation exercise for heart failure (HF) mainly focus on stable patients with chronic HF. Results from investigations that focus on the relationship between clinical outcomes and exercise during rehabilitation of patients with acute heart failure (AHF) have produced insufficient data. The aim of this study was to evaluate the correlation between clinical outcomes and dyspnea during in-hospital early rehabilitation in patients with AHF. Methods: Dyspnea was measured using a 5-point Likert scale (5PLS) during rest and at the initiation of upright sitting and standing. Dyspnea was defined as 5PLS ≥2. The primary endpoint was combined all-cause death or rehospitalization for HF. Results: A total of 221 patients were included in this study; 81 patients (37%) died or were hospitalized during the follow-up period. In patients with dyspnea during upright sitting and standing, the event-free ratio was significantly lower compared with patients without dyspnea ( P = .008 and P < .001, respectively). Body mass index (hazard ratio [HR] = 0.91, P = .011), noninvasive positive pressure ventilation usage (HR = 1.96, P = .042), and 5PLS ≥2 at the initiation of standing (HR = 2.63, P = .008) were detected as predictors of primary endpoint. New York Heart Association class IV at admission (OR = 3.17, P = .0114) and pre-admission Katz ADL index <6 (OR = 3.76, P = .0007) were isolated as risk factors for dyspnea when standing. Conclusions: Dyspnea during standing was associated with unfavorable events in patients with AHF as a comprehensive indicator. Abstract : We investigated the relationship between dyspnea during the rehabilitation program and adverse outcomes in patients with AHF. The primary endpoint was all-cause death or rehospitalization for HF. The event-free ratio was significantly lower in patients with dyspnea at standing, and dyspnea at standing was the predictor for unfavorable events.